The Link Between Dietary Habits and Body Mass Index in Relation to the Occurrence of Hypertension in The Jatiwarna Village Community Health Center - Manurung, Santa; Najiyah, Imtihani Afiyah; Krisanty, Paula; Pangestuti, Tri Endah; Wartonah, Wartonah; Yardes, Nelly; Sudrajat, Ace (Jurnal Keperawatan, 2024)
High blood pressure is a prevalent condition in the community and is a significant risk factor for heart disease. Hypertension is often called “the silent killer” because it is a highly perilous condition that can strike individuals without any detectable signs. There are various elements that can impact high blood pressure, such as dietary habits and obesity, which can be assessed by determining body mass index. To establish the correlation between dietary habits and BMI in relation to the prevalence of hypertension at the Jatiwarna Village Community Health Center. This investigation is a quantitative analysis with a cross-sectional methodology. The example utilized in this study consisted of 79 participants selected through the purposive sampling method. An examination of the connection between factors was conducted using chi square. The findings of the chi square analysis examination on the connection between diet and the occurrence of hypertension obtained p-value = 0,038 (<0,05) and an OR value = 3,117 and the correlation between body mass index and the occurrence of hypertension resulted in a p-value = 0.781 (greater than 0.05). There is a noteworthy connection between diet and the prevalence of hypertension and there is no substantial connection between body mass index and the prevalence of hypertension in adulthood.